The HPCSA must provide clearer guidelines on social media marketing for South African health professionals - Hopkins, Neil (My University, 2024)
There is a longstanding debate around the ethics and legality of advertising for health professionals. Recently advertising has seen a transition from traditional marketing towards social media marketing. Unfortunately, inappropriate social media marketing can result in exploitation, which is why guidelines are necessary to protect consumers from deceptive content. The Health Professions Council of South Africa (HPCSA) has published a set of ethical guidelines on social media. However, this report highlights that there is limited information in the guidelines pertaining to social media marketing. There is also no reference to South African legislation that should be considered when using social media marketing. The purpose of this report is to emphasise that the HPCSA has an ethical and legal obligation to create clearer social media marketing guidelines for South African health professionals. This report proposes that the HPCSA must update their social media guidelines to make them clearer and to provide more information on social media marketing
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Health professionals; Advertising; Ethical guidelines; South African health professionals